The duty of a Muslim in his dealings with the other, methods of advocacy as a model - Aliwi , Ehsan (Islamic Sciences Journal, 2023)
Islam took care of this topic and presented it to its adherents, under several titles that fall within this topic, and the origin of this topic was a course delivered to a group of students. It was from Allah’s grace that He facilitated for me a copy of the course material, so I wrote it, added to it and arranged it. I ask Allah to make my work pure for His honorable face. He is a generous horse, and the issue of dealing with the other is taken care of by all the peoples in the world, including the Islamic peoples, and the Westerners have special institutes in which the so-called social skills are taught, just as preachers must know before they carry out the call with the invitees what is the nature of the invitees and what is the method The most appropriate call with them, and how to deal with them.